Wali nikah dalam perspektif Imam Syafi’i dan Imam Hanafi - Ridho, Muhammad; Hannan, Abd (AL-MUQARANAH, 2023)
This paper discusses the marriage guardian in the review of Imam Syafii and Imam Hanafi. Wali nikah, as is known, is part of the issue of marriage whose existence is still in dispute. In a marriage, the concept of guardianship is an inseparable part because this is one of the legal requirements of Islamic marriage that must be fulfilled. Should a woman get married with a guardian? The majority of scholars require it, but for Imam Abu Hanifah, the status of a guardian in a marriage contract is sunnah, not fardlu, which can invalidate the marriage, except that the guardian has the right to approve the marriage or not. And women can be guardians in a marriage contract, besides that a woman who is an adult kamal al-ahliyyah can marry herself or be her representative. This paper is included in the type of library research, which is descriptive analysis. The data collection technique is by searching and collecting books and books as well as journals or blogs, especially those related to the study of this problem, then using the Ushul Fiqh approach and Qaidah Fiqhiyyah. Based on the results of the analysis conducted by the compiler, the results are as follows According to Imam Shafi'i, the presence of a guardian is one of the pillars of marriage, which means that without the presence of a guardian when doing a marriage contract the marriage is not valid. Imam Hanafi is of the opinion that if a woman does a marriage contract without a guardian, while her prospective husband is comparable (kufu'), then the marriage is permissible. She can marry herself and her minor daughter, and she can do so on behalf of someone else. But if the woman wants to marry a man who is not kufu', then the guardian can prevent her from doing so. According to the Hanafis, the presence of a guardian in a marriage is Sunnah.